Developing Reading Skills in Children Under Conditions of Bilingualism and Cultural Diversity - Sokolova, Olga (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
The article examines the structural and developmental specifics of reading skill formation in children growing up in conditions of bilingualism and cultural diversity. The objective of the study is to identify the cognitive and environmental predictors that determine differentiated trajectories of decoding and reading comprehension in multilingual contexts. To achieve this objective, an analytical synthesis of longitudinal and cross-sectional empirical studies was conducted, focusing on early phonological awareness, vocabulary development, print knowledge, migration background, home literacy exposure, and perceptual mediation mechanisms. Comparative analysis and structural reconstruction methods were applied to integrate heterogeneous findings into a coherent developmental model. The results demonstrate that phonological awareness operates as a transferable metalinguistic foundation supporting decoding across languages, whereas vocabulary functions as a language-specific predictor primarily shaping reading comprehension. Early disparities in vocabulary and phonological sensitivity tend to attenuate over time, indicating compensatory growth dynamics rather than cumulative divergence. Environmental exposure modifies the intensity of lexical development but does not replace foundational phonological mechanisms. The conclusion establishes that bilingual reading development follows a hierarchical organization in which transferable cognitive infrastructure interacts with language-bound lexical consolidation, producing adaptive recalibration across primary school years.